Bilan des connaissances sur la cardine (Lepidorhombus whiffiagonis ). Etude du stock de Mer Celtique. - Aubin-ottonheimer, G (ISTPM, 1985)
This study presents the biology of the species Lepidorhombus whiffiagonis (ecology, nutrition, sexuality, growth weight and length) and its exploitation with the balance of catches in North Atlantic and its fishing in Celtic Sea. Yield and fecundity per recruit related to the fishing effort are estimated. The influence of the mesh size modifications is analyzed. The impact of uncertainty on the values of the parameters modelling and individual variability within the growth is analyzed.